From Ruszczyc to the Iron Curtain: Studies in the History of the Faculty of Fine Arts of Stefan Batory University in Vilnius (1919–1939) - Michliński, Rafał (Lietuvos istorijos studijos, 2023)
Rec.: Małgorzata Geron (ed.), Wydział Sztuk Pięknych na Uniwersytecie Stefana Batorego w Wilnie (1919–1939/45): Dydaktyka, twórczość i tradycja artystyczna, Toruń: Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2022.